Languaging in mathematics classrooms – space for students’ varied language repertoires in the Language introduction program in Sweden - Wedin, Åsa (NOMAD Nordic Studies in Mathematics Education, 2021)
The aim for this article is to investigate how languaging in mathematics classrooms for recently arrived students may or may not support students’ development of mathematics language and thinking. The study builds on classroom observations with four teachers in upper secondary school in Sweden, and the analysis is based on languaging as a source of meaning. Generally, students did not ask many questions and it was only in two classrooms that students were required to talk mathematics and to move between different representations. A space open for students’ use of their varied linguistic repertoires appeared. However, whether teachers themselves took part in the ongoing translanguaging practices or not influenced what value these practices were attributed. The article highlights the need for teachers to be educated in the role of languaging in mathematics and in conditions for learning among recently arrived students and students who study school subjects through a second language that they are in the beginning of learning.